MENGATASI MOTIVASI BELAJAR RENDAH SISWA DENGAN TEKNIK BEHAVIORAL - Jayadi Jayadi; Gita Anggraini; Dina Juniarti (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2020)
Motivation is very important in students to increase interest in learning. In fact there are students who do have low motivation in learning which impacts on their learning outcomes. This study aims to improve low learning motivation at MA Nurul Ummah sampit by applying a Behavioral approach. This research is a qualitative study with a case study approach. Data collection in this study uses interview, observation and documentation. The object of this study is low learning motivation. The subject of this study was one of the XII students at MA Nurul Ummah Sampit. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. For data validity checking techniques are using source triangulation and method triangulation. The results of this study indicate that the application of Behavioral techniques succeeded in increasing low learning motivation. The increase in motivation of students from low categories becomes a high category after carrying out individual counseling.